Leech’s Meanings in Robert Burns’ Poem “A Red, Red Rose” - Jimmi - - (Universitas Veteran Bangun Nusantara, 2022)
Meaning can be revealed with types of meaning. The identification of the meaning is included in the semantic realm. Semantics is a branch of linguistics that deals explicitly with meaning. Disclosure of any meaning contained in a poem is a challenge. There are seven types of meaning proposed by Leech's. Then it can be raised to question what are meanings within the poem